Peri- and postoperative complications of laparoscopic tubal ligation versus salpingectomy for permanent contraception: An ACS-NSQIP analysis - Vaishnavi J. Patel; Devki Patel; Kimberly Toumazos; Young Son; Komal Sharma; Virgil Kevin DeMario; Shelby Boock; Grace Lara; Alexandra McQuillen; Brianna Clark (Laparoscopic, Endoscopic and Robotic Surgery)
Objectives: Salpingectomy and tubal ligation are commonly performed for permanent contraception in women. Salpingectomy has been suggested to reduce the risk of ovarian cancer, but its comparative operative and perioperative risks have not been well established. The objective of this study is to compare the peri- and postoperative complications of laparoscopic tubal ligation with those of salpingectomy for permanent contraception. Methods: A retrospective review of 49,445 patients who underwent laparoscopic salpingectomy or tubal ligation for permanent contraception between 2017 and 2021 was conducted using data from the American College of Surgeons National Surgical Quality Improvement Program database. Statistical analysis involved t test, chi-square test, and logistic regression analysis with the use of the random forest algorithm. The primary outcomes were perioperative and postoperative complications. Results: Of the total cohort, 45,307 (91.6%) underwent laparoscopic salpingectomy, and 4138 (8.4%) received laparoscopic tubal ligation. There were significant differences between the salpingectomy and tubal ligation groups with respect to several demographic characteristics, including age, BMI, minority status, and variations in past medical history. These demographic characteristics were controlled for in the multivariate regression analysis. Salpingectomy had a higher rate of operative and postoperative complications than did tubal ligation (OR = 1.78, 95% CI: 1.46–2.20, p < 0.001). Salpingectomy was associated with a greater risk of longer operation time (OR = 2.03, 95% CI: 2.02–2.04, p < 0.001), longer hospital stay (OR = 5.26, 95% CI: 4.57–6.09, p < 0.001), increased readmission (OR = 3.15, 95% CI: 1.92–5.65, p < 0.001), and increased unplanned reoperation (OR = 2.42, 95% CI: 1.32–5.12, p = 0.010). In addition, the occurrence rates of organ space surgical site infection (OR = 2.68, 95% CI: 1.21–7.59, p = 0.032) and sepsis (OR = 3.93, 95% CI: 1.48–16.02, p = 0.020) were significantly greater in the salpingectomy group than in the tubal ligation group. Conclusions: Laparoscopic tubal ligation and salpingectomy are both safe and effective procedures for permanent contraception; however, salpingectomy is more likely to be associated with peri- and postoperative complications. These findings may help guide clinical decision-making when selecting the optimal permanent contraception method for women.